Development of 3rd generation Medium Mn duplex steels for automotive applications. Issue 2 (22nd January 2019) - Perlade, Astrid; Antoni, Annie; Besson, Rémy; Caillard, Daniel; Callahan, Michael; Emo, Jonathan; Gourgues, Anne-Françoise; Maugis, Philippe; Mestrallet, Aurore; Thuinet, Ludovic; Tonizzo, Quentin; Schmitt, Jean-Hubert
ABSTRACT: The mechanical behaviour and fracture were studied in a Fe–5Mn–2.5Al–0.2C (in wt-%) Medium Mn steel. Metallographic and magnetic measurements confirm the significant influence of the transformation kinetics of the strain-induced martensite on the mechanical properties and strain heterogeneities (Lüders and Portevin-Le Chatelier-like phenomena). An accurate study of isothermal evolutions of the microstructure, associated with atomistic calculations, complements current thermodynamic databases to quantify the nature and volume fraction of phases at different temperatures. A kinetic approach then predicts the influence of annealing conditions on the composition of retained austenite, key parameter for the martensitic transformation kinetics. This supports quantitative modelling of the influence of the intercritical annealing temperature on the ultimate tensile strength for industrial developments of these new grades.